A methodological framework for assessing agreement between cost-effectiveness outcomes estimated using alternative sources of data on treatment costs and effects for trial-based economic evaluations. - Achana, F; Petrou, S; Khan, K; Gaye, A; Modi, N; Medicines For Neonates Investigators (Springer, 2017)
A new methodological framework for assessing agreement between cost-effectiveness endpoints generated using alternative sources of data on treatment costs and effects for trial-based economic evaluations is proposed. The framework can be used to validate cost-effectiveness endpoints generated from routine data sources when comparable data is available directly from trial case report forms or from another source. We illustrate application of the framework using data from a recent trial-based economic evaluation of the probiotic Bifidobacterium breve strain BBG administered to babies less than 31 weeks of gestation. Cost-effectiveness endpoints are compared using two sources of information; trial case report forms and data extracted from the National Neonatal Research Database (NNRD), a clinical database created through collaborative efforts of UK neonatal services. Focusing on mean incremental net benefits at £30,000 per episode of sepsis averted, the study revealed no evidence of discrepancy between the data sources (two-sided p values >0.4), low probability estimates of miscoverage (ranging from 0.039 to 0.060) and concordance correlation coefficients greater than 0.86. We conclude that the NNRD could potentially serve as a reliable source of data for future trial-based economic evaluations of neonatal interventions. We also discuss the potential implications of increasing opportunity to utilize routinely available data for the conduct of trial-based economic evaluations.